(untitled) (Journal of Global Accounting, 2024)
The study ascertained the effect of firm attributes on audit report timeliness among listed consumer goods firms in Nigeria. The specific objective was to determine the extent to which firm profitability, firm size and firm leverage affect the timeliness of audit report among listed consumer goods firms in Nigeria. The study used ex-post facto research design. The population of the study was all the twenty-one (21) listed consumer goods firms on the Nigerian Exchange Group from which a sample size of sixteen (16) was obtained using purposive sampling. The study employed secondary data that were extracted from audited financial statements and annual reports of individual consumer goods firms from 2014 to 2023. The hypotheses formulated were tested using panel regression technique at 5% level of significance. The study found that: firm profitability has a significant negative effect on audit report timeliness among listed consumer goods firms in Nigeria (p-value =0.000); firm size has a non-significant negative effect on the timeliness among listed consumer goods firms in Nigeria (p-value = 0.5061); firm leverage has a non-significant negative effect on the timeliness among listed consumer goods firms in Nigeria (p-value = 0.7644). In conclusion, it takes longer time to publish audit reports of consumer goods firms that have higher profits, more debts and more assets. The study recommends that audit committees and financial managers should consider implementing streamlined auditing processes tailored to the specific complexities associated with profitable operations by enhancing communication channels between auditors and internal teams to expedite the review of financial statements and disclosures.